Personal data protection: The future arrived a while ago (Nueva Epoca, 2025)
This paper addresses the current importance of defending the right to personal data as part of the core of fundamental human rights, in the context of the rapid development of new technologies for collecting, processing, and transmitting metadata.
Keywords: Personal Data Rights; means of protection; new techs; metadata; consumer rights